State-Dependent or Time-Dependent Pricing? New Evidence from a Monthly Firm-Level Survey: 1980-2017 - Huw D. Dixon; Christian Grimme (Center for Economic Studies and ifo Institute (CESifo), 2019)
We take a monthly panel of German firms over the period 1980–2017 to examine the relative importance of time and state dependence in the decisions of firms to raise, lower or leave their price constant. In addition, we seek to estimate the relative importance of macroeconomic factors and firm-specific factors within state dependence. While price decreases can be well explained by time dependence alone, price increases are best predicted by the interaction of time-dependent and firm-specific state factors. Whilst on their own macroeconomic variables might seem important, once we add firm-specific variables the effects of macroeconomic variables become much smaller in magnitude. Our empirical results suggest that theoretical models should integrate both time and state dependence rather than developing the approaches separately. We also show that time dependence is better captured if we allow for different hazard functions for price increases and decreases.
Keywords: E30; E31; E32; 330; survey data; price setting; extensive margin; state-dependent pricing; time-dependent pricing